Marisha Rasi-Koskinen, the rebellious pen - United Nations Educational, Scientific; Cultural Organization; Anuliina Savolainen (The UNESCO Courier, 2024)
An award-winning author and school psychologist with a punk past, Marisha Rasi-Koskinen is a unique figure in Finnish literature. Young readers love her ambitious books, which explore issues that concern them without taboos.